2021
DOI: 10.1097/nmc.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Analysis of Childbearing Experiences During the COVID-19 Pandemic

Abstract: Purpose: The COVID-19 pandemic has disrupted health care delivery and services around the world causing rapid changes to maternity care protocols and pregnant women to give birth with tight restrictions and significant uncertainties. There is a gap in evidence about expectant and new mothers' experiences with birthing during the pandemic. We sought to describe and understand pregnant and new mothers' lived experiences during the COVID-19 pandemic using authentic birth stories. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…ernal me Globally, consistent findings have been reported concerning the impact of the pandemic on maternal mental health (3,(11)(12)(13)(14)(15)…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 56%
See 3 more Smart Citations
“…ernal me Globally, consistent findings have been reported concerning the impact of the pandemic on maternal mental health (3,(11)(12)(13)(14)(15)…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 56%
“…using keywords -Table 1 to identify existing literature to map out the impact of the pandemic on maternal mental health in Africa. Not surprising; however, we found only fourtwo articles from On the other hand, Pandey (2020) in Ethiopia conducted a hospital-based analysis of 178 women seeking perinatal services using the general anxiety disorder (GAD -7) (15). In this study, the prevalence of general anxiety disorder was 32.2%-a higher rate than was found in China (7).…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, elevated levels of depression (EPDS score > 13) were found in 40.7% of the women during the pandemic vs. 15% pre-pandemic. In addition, changes in obstetric guidelines and birth plans and worries about contracting the virus and its effect on the fetus among birthing people are associated with being stressed, worried, or anxious [14]. Moreover, maternal mental health disorders lead to negative lifelong consequences for mothers, infants, and families [12,13].…”
Section: Evidence Of Poor Mental Health Among Mothers In Covid-19mentioning
confidence: 99%